If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8(4-2)=4(3-5x)+2x
We move all terms to the left:
8(4-2)-(4(3-5x)+2x)=0
We add all the numbers together, and all the variables
-(4(-5x+3)+2x)+82=0
We calculate terms in parentheses: -(4(-5x+3)+2x), so:We get rid of parentheses
4(-5x+3)+2x
We add all the numbers together, and all the variables
2x+4(-5x+3)
We multiply parentheses
2x-20x+12
We add all the numbers together, and all the variables
-18x+12
Back to the equation:
-(-18x+12)
18x-12+82=0
We add all the numbers together, and all the variables
18x+70=0
We move all terms containing x to the left, all other terms to the right
18x=-70
x=-70/18
x=-3+8/9
| 13=1/5x+10 | | 14x+4=30x | | 19=-1.3x+-3.1 | | 7=f+13/6 | | 12+6x=90 | | -6+14x=13x+3 | | Y=-4.9t^2+30t+6 | | 4p/6-1=8 | | -4+21x=25x | | 41/4=2/3(z) | | 8x-4x=10-2x | | 1.68*t+5.25=18.69 | | 9x-1=17+7x | | 13y-15y=48 | | 13y=7y+42 | | 250=25z | | 325/y=13 | | 3y-18=27 | | x-0,04x=943 | | 17+7x=9x-1 | | 2/3(z)=41/4 | | p+46/9=9 | | 6-2a=8-2a | | -7(9-k)=77 | | 4.25*h=38.25 | | 6+3y=33 | | 2(x+1)+6=20-3(x)x=4 | | -2v-7/2v=11/2 | | -4+21x=19x+8 | | (–2x+4)=(4x+6) | | 23a-23a=0 | | 5x−1=2(3x+2) |